Latin American International Political Economy: contributions beyond the transatlantic divide - (:unkn) unknown (Oxford University Press, 2024)
The way in which international political economy (IPE) developed in Anglo-Saxon countries set the main standards for its study in other regions of the world, establishing a transatlantic order that separated mainstream IPE from the periphery. This articl...
Keywords: Economía política internacional; América Latina